Seven seas sop up CO2 [CO2 in the oceans]. - Evans, M.
Oceanographers and atmospheric scientists were pretty sure that the oceans must have taken up most of the missing CO2, but it is only with the completion of the latest study that this belief is confirmed by solid empirical evidence. The major findings are, first, that nearly half of the carbon dioxide that humans have pumped into the atmosphere over the last 200 years has been absorbed by the oceans, and, second, that the rising CO2 concentrations could start to have empirically filling a link in the general model of where CO2 originates and where it ends up, is that between 1800 and 1994, the ocean absorbed 48 percent of total CO2 emissions serious adverse effects on some marine life. In the case of the oceans, increasing the CO2concentration boosts acidity, which is neutralized when CO2reacts with calcium carbonate and water to form ions of HCO3 and calcium. And the reverse is true as well, with the ions reacting to form CO2, water, and calcium carbonate. In the face of increased acidity from rising CO2levels, the ocean tries to maintain its equilibrium by increasing the rate of reaction in the direction of making more ions. But that means consuming more calcium carbonate, which unfortunately for ocean life is the stuff of bone, shell, and coral.
Keywords: Acidity; Anthropogenic carbon dioxide; Carbon dioxide emissions; Marine life; Ocean chemistry; pH budget